Science Processing Skill and Critical Thinking: Reviewed Based on the Gender - Darmaji, Darmaji; Kurniawan, Dwi Agus; Astalini, Astalini; Setiya Rini, Endah Febri (Jurnal Pendidikan Indonesia, 2022)
Skills are an essential aspect that every individual should have. One of the critical skills essential in making education and employment successful in the 21st century is critical thinking skills. A person with critical thinking skills can search for understand, and evaluate a statement by analyzing logical and rational relevant matters in problem-solving or decision-making processes. This study aims to analyze the influence of science process skills on critical thinking skills. The sampling technique used is total sampling, with a sample of 60 practicants. This research is descriptive quantitative research with experimental methods through observation sheet instruments and essay test. Data analysis techniques were used, namely descriptive statistics and inferential statistics. The data analysis obtained science process skills of grade VII students at SMPN 8 Batanghari have been categorized as good, but more dominant in female students with a percentage of 79.5%. Meanwhile, critical thinking skills have also been classified as critical and dominant in female students, 46.2% in the highly critical category. Based on the study results, obtained p-value 0.000/2= 0.000, 0.000<0.05, meaning there is an influence of science process skills on students' critical thinking skills. It is hoped that this research can contribute to schools in Indonesia.